2018
DOI: 10.3847/1538-4357/aaae63
|View full text |Cite
|
Sign up to set email alerts
|

The Next Generation Virgo Cluster Survey (NGVS). XXXII. A Search for Globular Cluster Substructures in the Virgo Galaxy Cluster Core

Abstract: Substructure in globular cluster (GC) populations around large galaxies is expected in galaxy formation scenarios that involve accretion or merger events, and it has been searched for using direct associations between GCs and structure in the diffuse galaxy light, or with GC kinematics. Here, we present a search for candidate substructures in the GC population around the Virgo cD galaxy M87 through the analysis of the spatial distribution of the GC colors. The study is based on a sample of ∼ 1800 bright GCs wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 59 publications
1
11
0
Order By: Relevance
“…Observations of the GC population outside 30 kpc of the centre of M31 have shown that a large fraction of these GCs are situated on streams (Mackey et al 2010) and this has also been found to be the case for other galaxies outside the Local Group (e.g. Romanowsky et al 2012;Powalka et al 2018). As is the case for the Sagittarius dwarf, our simulations predict that the mean age of these GCs is younger than the other GCs associated with these galaxies.…”
Section: Comparisons With Observationssupporting
confidence: 74%
“…Observations of the GC population outside 30 kpc of the centre of M31 have shown that a large fraction of these GCs are situated on streams (Mackey et al 2010) and this has also been found to be the case for other galaxies outside the Local Group (e.g. Romanowsky et al 2012;Powalka et al 2018). As is the case for the Sagittarius dwarf, our simulations predict that the mean age of these GCs is younger than the other GCs associated with these galaxies.…”
Section: Comparisons With Observationssupporting
confidence: 74%
“…The Hα filament is located at the southeast edge of the cavity formed by the counter-jet. (Powalka et al 2018), seem to suggest that the ionised gas filament is the remnant of a gas-rich galaxy which has recently been accreted by M 87, as first proposed by Sparks et al (1993), or has crossed the halo losing most of its gas reservoir after a rampressure-stripping event (Mayer et al 2006). The rough estimate of the total mass of the ionised gas in the filament (M filament 6.9 × 10 7 M ) is comparable to that of the gas that would have been associated with the observed dusty filaments if this dust had been accreted from an external object (M gas,dust 2 × 10 7 M ).…”
Section: The Origin Of the Filamentmentioning
confidence: 99%
“…11). This analysis was motivated by the recent finding of a correlation between GC color-color relations and environment, and interpreted as driven by different stellar abundance ratios (Powalka et al 2016b(Powalka et al , 2018, altough interpretations related to different underlying ages are also given, e.g. Usher et al (2015); Powalka et al (2018) ).…”
Section: Photometric Propertiesmentioning
confidence: 99%